ANGPTL4 inhibits granulosa cell proliferation in polycystic ovary syndrome by EGFR/JAK1/STAT3‐mediated induction of p21. Issue 2 (6th January 2023) - Jiang, Qi; Miao, Ruolan; Wang, Yuhuan; Wang, Wenqi; Zhao, Dingying; Niu, Yue; Ding, Qiaoqiao; Li, Yan; Leung, Peter C. K.; Wei, Daimin; Chen, Zi‐Jiang
Abstract: Polycystic ovary syndrome (PCOS) is one of the most common, heterogenous endocrine disorders and is the leading cause of ovulatory obstacle associated with abnormal folliculogenesis. Dysfunction of ovarian granulosa cells (GCs) is recognized as a major factor that underlies abnormal follicle maturation. Angiopoietin‐like 4 (ANGPTL4) expression in GCs differs between patients with and without PCOS. However, the role and mechanism of ANGPTL4 in impaired follicular development are still poorly understood. Here, the case–control study was designed to investigate the predictive value of ANGPTL4 in PCOS while cell experiments in vitro were set for mechanism research. Results found that ANGPTL4 levels in serum and in follicular fluid, and its expression in GCs, were upregulated in patients with PCOS. In KGN and SVOG cells, upregulation of ANGPTL4 inhibited the proliferation of GCs by blocking G1/S cell cycle progression, as well as the molecular activation of the EGFR/JAK1/STAT3 cascade. Moreover, the STAT3‐dependent CDKN1A (p21) promoter increased CDKN1A transcription, resulting in remarkable suppression effect on GCs. Together, our results demonstrated that overexpression of ANGPTL4 inhibited the proliferation of GCs through EGFR/JAK1/STAT3‐mediated induction of p21, thus providing a novel epigenetic mechanism for the pathogenesis of PCOS.